PARTISIPASI MASYARAKAT TERHADAP KEBERADAAN HUTAN MANGROVE DI DESA PERCUT KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG (Society Participation Against the Existence of Mangrove Forest in Percut, Percut Sei Tuan Sub district, Deli Serdang Regency) - Uswatun Nisa; Darma Bakti; Febrina Arli (AQUACOASTMARINE, 2016)
Mangrove forest in Percut, Percut Sei Tuan sub district, Deli Serdang regency be degraded and damaged due to human activities and nature process. This study focused on community participation level toward the existence of mangrove forest in the Percut. The objective of study was to determine the existence of relationship between the identity of individual with community participation and the constraints that affect community participation. This study was conducted on April to May 2016. In taking the sample, the researcher used purposive sampling method which was done by conducted interviews and distributing questionnaires to community in mangrove areas, in Percut. The result showed that community participation toward the existence of mangrove forest is in average level with the 58.65% index. It means that there is no significant relationship between the identity of individual (age, number of family members, long living, and education) and community participation. So, the identity of individual such as income and job showed that they have significant relationship with community participation toward the existence of the mangrove forest.Keywords: Community Participation, Identity of Individual, Mangrove Forests